Pengaruh Penggunaan Media Pembelajaran Kahoot Berbasis Game Based Learning Terhadap Hasil Belajar Siswa pada Mata Pelajaran Informatika di SMK Negeri 2 Maros - A. Nurul Fitri; Nining Anggreini; Andi Quraissy; Ramliah Ramliah; Nasir Nasir (Institut Nalanda, 2024)
This research aims to test whether there is an influence of the use of Game-based Learning media Kahoot on student learning outcomes in informatics subjects at SMK Negeri 2 Maros. Sampling used a purposive samplingtechnique. The sample taken was class X TKJT A with a total of 34 students. This research uses one independent variable, namely the use of Kahoot learning media (X) and one dependent variable, namely learning outcomes (Y). This research method uses pre-experiment, one group pretest and posttest. The data analysis technique used in this research is descriptive statistical analysis. The results of this research show that the significance value (Sign.) is 0.001, which means less than 0.05. The use of Kahoot learning media based on game based learning in informatics subjects can influence student learning outcomes at SMK Negeri 2 Maros. This can be proven by increasing student learning outcomes through pretest and posttest activities, where students can achieve an average score of 62.20% without treatment and students can achieve a score of 87.64% after treatment. So there was an increase in student scores of 25.44%..